Effect of Intercropping Barley and Berseem on vegetative growth and productivity - Mohamed Abdalla Emhemmed Hussain (African Journal of Advanced Pure and Applied Sciences, 2026)
The field experiment was conducted at Abu Hadi area-Sirte city, during the winter season 2022-2023 to study the effect of humic acid on vegetative growth and productivity of three cuts of sole barely, sole berseem and their mixture. The experimental design was spilt-spilt plot Design with three replicates: the main plot were allocated to forage crops with sole barley (Hordeum vulgare, L.) cv., Giza 2000, at rate 123.55 kg/ha, berseem (Trifolium alexandrinum, L.) cv., Giza 6, at rate 61.78 kg/ ha, and mixture plants (65% berseem +35 barley) with rate 46.33 kg berseem/ ha + 30.89 kg barley/ ha, the seeds of barley and berseem were mixed at the previous rate and planted by broadcasting on the surface. Three levels of humic acids by rate 3 ,6 and 9 kg/ha, occupied in sub-plot as ground application during the preparing of sowing and three cuts were distributed in sub-sub plot which were taken in season after 60, 90 and 120 day from sowing. Studied characters were vegetative growth i.e. (plant height, number of tillers- branches /m2, fresh weight (kg/ha) and dry weight (kg/ha) and yield quality (grain yield (kg/ha), straw yield (kg/ha), biological yield (kg/ha), protein and carbohydrates percentages. Results showed mixture of forage plants produced the best values in all vegetative characters under studied, also, humic acid at 9 kg/ha recorded highest all vegetative growth and 3rd cut surpassed 1st and 2nd cuts in 2022-2023 season. Whereas, Sole barley gave the highest grain yield, while, mixture of forage plants gave the height values of straw yield, biological yield, protein and carbohydrates percentages. Humic acid at 9 kg/ha recorded highest all vegetative characters and yield quality were studied. The highest value for all parameters (vegetative growth and yield quality) were observed under mixture forage plants in the third cut with humic acids at rate 9 kg/ha. The interactions among forage crops and humic acid was highly significantly, also, forage crops and cuts was highly significantly, humic acid and cuts was highly significantly and interaction between forage crops, humic acid and cuts was highly significantly on all vegetative growth and yield quality characters.